Analysis of Consumer Behavior in The Use of Fintech Digital Payment Systems - Afrizal, Rizki Adi; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2025)
The development of digital technology has brought significantts changes in various aspects of life, including in the consumption patterns of society. The ease of access to digital financial services through Financcial Technology (Fintech), particularly digital payment systems like OVO, Gopay, Dana and Shopeepay, contributes to the increase in consumer behavior, especially among students. This study aims to determine the influence of consumer behavior on the use of Fintech Digital Payment Service among Accounting Educations Students at University of Muhammadiyah Surakarta. The research method used is a quantitative approach with an ethnographic design, involving 109 randomly selected respondents. Data analysis techniques were conducted using normality test, linearity tests, and partial tests (t-test). This research results show that consumer behavior has a significant impact on the use of Fintech Digital Payment with a significance value of 0.000 (< 0.05) and t-value of 4.993 > t-table 1.985. These findings indicate that the higher the consumer behavior of students, the greater their tendency to use digital payment services. The ease of transactions, the presence of promotions and discounts, and the accesbility of technology are the main triggers. Therefore, improving financial literacy is essential to control student’s consumer behavior in the face of convenience of financial technology.